IMMEDIATE ADVERSE DRUG EVENTS WITH RITUXIMAB THERAPY IN NON-MALIGNANT HEMATOLOGICAL DISORDERS - Neetha, Alice; Panicker, Naveen Kumar; Sidharthan, Neeraj (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: Rituximab therapy has become a promising therapeutic option for various non-malignant hematological disorders, after being reported by many case reports. The objective of this study was to evaluate the immediate, infusion-related adverse drug events (ADE) of patients who received rituximab for non-malignant, hematological disorders, in a tertiary healthcare center in India. Methods: 14 patients (6 with primary immune thrombocytopenia, 4 with autoimmune hemolytic anemia, 3 with thrombotic thrombocytopenic purpura, 1 with acquired hemophilia) were enrolled in the study. Patients were assessable for immediate infusion-related toxicity noted predominately within 5 hrs of administration of rituximab infusion. Results: Rituximab therapy was tolerated without major ADE. None of the patients experienced high-grade adverse events. The population who experienced ADE (Grades 1-2) frequently had toxicities that suspected to result from infusion-related cytokine release syndrome (IRCRS) and sometimes required cessation of the infusion and supportive intervention. Patients were monitored for 20 types of ADEs associated with IRCRS. 11 types of; mild to moderate (Grades 1 and 2) toxicities resulting from IRCRS were experienced by patients. Mean patients who experienced IRCRS was 1.95 (13.93%), whereas majority of the study population tolerated therapy without IRCRS (86.78%). Among other toxicities, Grade 2 urinary tract infection (UTI) (n=2, 14.29%); Grade 2 hyperglycemia (n=1, 7.14%) and Grade 1 myalgia (n=1, 7.14%) were observed. Conclusion: Toxicity profile of patients with non-malignant hematological disorders shows that rituximab is a safer biological therapy. Keywords: Rituximab, Infusion related cytokine release syndrome, Adverse drug events, Immediate toxicities, Benign, Non-malignant, Hematological disorders.